Physical Resource Mobilisation and Internal Efficiency of Technical Training Institutions in Bungoma County - Wakoli, Maximilla; Julius Maiyo,; Alice Limo , (IJRDO- Journal of Educational Research, 2019)
Because of limited resources (physical) being availed to public Technical Training Institutions (TTIs) around the world, as a way of ensuring quality TVET provision, institutions are required to mobilise additional resources. This paper looks at how public TTIs in Bungoma County Kenya were mobilising physical infrastructural resources to ensure achievement of internal efficiency goals. This is because for long, incidents of low internal efficiency have been a common trend in majority of public TTIs in Kenya and beyond. This study was conducted in four public TTIs which are located in Bungoma County. The study methodology was mixed which incorporated both qualitative and quantitative approaches. The respondents for the study consisted of the four public TTIs principals, 16 resource mobilisation officials of the said institutions and 239 faculty members (tutors). The respondents were selected through purposive and stratified random sampling technique. To collect data, questionnaire, and interview and document checklist were used. The research instruments were tested for validity and reliability. The outcomes revealed that